2006
DOI: 10.2119/2006-00037.zheng
|View full text |Cite
|
Sign up to set email alerts
|

CD151 Gene Delivery Activates PI3K/Akt Pathway and Promotes Neovascularization after Myocardial Infarction in Rats

Abstract: Our previous study showed that CD151 promotes neovascularization and improves blood perfusion in a rat hindlimb ischemia model. In this study, we investigated whether CD151 promotes neovascularization and improves ventricular function after myocardial infarction in rats and the mechanisms involved. Rats were subjected to sham surgery or coronary artery ligation. We used rAAV for direct delivery of the human CD151 gene into the rat myocardium. At 4 weeks after coronary artery ligation, human CD151 mRNA was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Exogenous nerve growth factor supports angiogenesis and myocyte survival in infarcted murine hearts via the AKT/FOXO pathway (78, 475). CD151 induces endothelial cell proliferation, migration, and neovascularization in infarcted hearts via PI3K/AKT activation (695, 696), while periostin signals through FAK and AKT to mediate recruitment of activated cardiac fibroblasts to sites of cardiac injury following acute myocardial infarction (581). Intracardiac injection of SDF-1a into infarcted mouse heart improves cardiomyocyte survival and increases neoangiogenesis, potentially via activation of AKT (572).…”
Section: Akt In the Myocardial Contextmentioning
confidence: 99%
“…Exogenous nerve growth factor supports angiogenesis and myocyte survival in infarcted murine hearts via the AKT/FOXO pathway (78, 475). CD151 induces endothelial cell proliferation, migration, and neovascularization in infarcted hearts via PI3K/AKT activation (695, 696), while periostin signals through FAK and AKT to mediate recruitment of activated cardiac fibroblasts to sites of cardiac injury following acute myocardial infarction (581). Intracardiac injection of SDF-1a into infarcted mouse heart improves cardiomyocyte survival and increases neoangiogenesis, potentially via activation of AKT (572).…”
Section: Akt In the Myocardial Contextmentioning
confidence: 99%
“…The a6b4 and a3b1 integrins regulate the migration of epithelial cells through a direct interaction of these integrins with the C-terminal domain of netrin-1, and the modulatory activity of CD151 is dependent on its association with the a3b1 and a6b4 integrins [23,24]. CD151 was shown to promote neovascularization and angiogenesis in a rat model of hindlimb ischemia and to improve ventricular function after myocardial infarction in rats [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, overexpression of CD151 in human umbilical vein ECs enhances cell proliferation, migration, and capillary tube formation on Matrigel [22] . We have reported that CD151 gene delivery increased the number of microvessels in a rat myocardial ischemia model and a rat ischemic hindlimb model [1,2] . Further study underlined that CD151 gene delivery promoted angiogenesis in a pig myocardial ischemia model and demonstrated that CD151-induced neovascularization effectively enhanced the myocardial perfusion and markedly ameliorated the regional myocardial dysfunction based on 13 N-NH 3 PET imaging and echocardiography [3,4] .…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies have demonstrated that direct injection of an AAV vector carrying CD151 gene to rat ischemic hind limb induced neovasculature formation, and CD151 gene delivery increased the number of microvessels in a rat ischemic myocardium model [1,2] . Further study indicated that CD151 gene delivery induced angiogenesis by increasing the capillary and arteriole density in a swine myocardial infarction model [3,4] .…”
mentioning
confidence: 99%